Investment Committee, Corporate Cash Holdings and Corporate Life Cycle - Eulaiwi, Baban; Al-Hadi, Ahmed; Hussain, S.; Al-Yahyaee, K. (Wiley-Blackwell Publishing Asia, 2018)
© 2018 International Review of Finance Ltd. 2018 We investigate the association between voluntary formation of board investment committee (IC) and corporate cash holdings of nonfinancial firms over the corporate life cycle stages for a large sample of Gulf Cooperation Council firms during 2005–2016. We find that IC increases corporate cash holdings in growth and maturity stages of firm, compared to introduction, shake-out, and decline stages. These results have important implications for investors, policy makers, and regulators. Our findings are robust to various econometrics specifications.